In vitro characterisation of murine pre‐adipose nucleated cells reveals electrophysiological cycles associated with biological clocks. Issue 12 (22nd May 2022) - Martin, Capucine; Johnston, Jonathan D.; Henslee, Erin A.; van der Veen, Daan R.; Labeed, Fatima H.
Abstract: Adipocytes are energy stores of the body which also play a role in physiological regulation and homeostasis through their endocrine activity. Adipocyte circadian clocks drive rhythms in gene expression, and dysregulation of these circadian rhythms associates with pathological conditions such as diabetes. However, although the role of circadian rhythms in adipose cells and related tissues has been studied from phsyiological and molecular perspectives, they have not yet been explored from an electrical perspective. Research into electro‐chronobiology has revealed that electrical properties have important roles in peripheral clock regulation independently of transcription–translation feedback loops. We have used dielectrophoresis to study electrophysiological rhythms in pre‐adipocytes – representing an adipocyte precursor and nucleated cell‐based model, using serum shocking as the cellular method of clock entrainment. The results revealed significant electrophysiological rhythms, culminating in circadian (ca. 24 hourly) cycles in effective membrane capacitance and radius properties, whereas effective membrane conductance was observed to express ultradian (ca. 14 hourly) rhythms. These data shed new light into pre‐adipocyte electrical behaviour and present a potential target for understanding and manipulation of metabolic physiology.